Long-term outcome of severe alveolar haemorrhage in ANCA-associated vasculitis: a retrospective cohort study. (May 2013) - Hruskova, Z; Casian, AL; Konopasek, P; Svobodova, B; Frausova, D; Lanska, V; Tesar, V; Jayne, DRW
<x xml:space="preserve">Abstract</x> Objectives: Alveolar haemorrhage (AH) is a major cause of early death in anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). There is a paucity of information regarding the outcomes of AAV patients presenting with severe AH. Method: A retrospective cohort study. Patients with severe AH were identified from a case review of 824 AAV patients. Demography, presenting features, treatment, and outcomes are described. Results: Fifty-three patients (33 males, 20 females; median age 59 years) with severe AH were identified: 37 (69.8%) with granulomatosis with polyangiitis (Wegener's) and 16 with microscopic polyangiitis [36 proteinase 3 (PR3)-ANCA positive and 17 myeloperoxidase (MPO)-ANCA positive]. AH was the first disease manifestation in 46 (86.8%) patients. Assisted ventilation was required in 36 (67.9%), renal involvement was present in 52 (98.1%), and 28 (52.8%) required dialysis. Forty (75.5%) received plasma exchange. At 3 months, 44/53 (83.0%) were alive. The mean follow-up was 49 months when 31 (58.5%) were alive and 24 (45.3%) dialysis independent. Mortality was higher in those requiring dialysis at entry (57.1% vs. 24%, p = 0.02) and in patients aged > 65 years (71.4% vs. 30.8%, p = 0.01), and tended to be higher in those requiring intubation (54.5% vs. 32.2%, p = 0.1). Conclusions: Severe AH was more commonly associated with PR3-ANCA (vs. MPO-ANCA) and strongly correlated with renal vasculitis. Current treatment of severe AH leads to remission but long-term mortality remains high. Concurrent renal failure and older age were associated with higher mortality.